2015
DOI: 10.1007/s00441-015-2213-9
|View full text |Cite
|
Sign up to set email alerts
|

INSL3 stimulates spermatogonial differentiation in testis of adult zebrafish (Danio rerio)

Abstract: INSL3 (insulin-like peptide 3) is a relaxin peptide family member expressed by Leydig cells in the vertebrate testis. In mammals, INSL3 mediates testicular descent during embryogenesis but information on its function in adults is limited. In fish, the testes remain in the body cavity, although the insl3 gene is still expressed, suggesting yet undiscovered, evolutionary older functions. Anti-Müllerian hormone (Amh), in addition to inhibiting spermatogonial differentiation and androgen release, inhibits the Fsh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 47 publications
3
78
0
Order By: Relevance
“…To estimate the relative mRNA expression levels of a number of selected genes (Supplemental Table 1) by validated real-time, quantitative PCR (qPCR) assays, samples were processed as previously described (35,36). To visualize the cellular expression sites of igf3 mRNA in zebrafish testis, in situ hybridization (ISH) was carried out as described previously (37), using DIG-labeled sense and antisense cRNA synthesized from a igf3-specific PCR product generated with primers 2878 -2879 (Supplemental Table 2). …”
Section: Testicular Gene Expressionmentioning
confidence: 99%
“…To estimate the relative mRNA expression levels of a number of selected genes (Supplemental Table 1) by validated real-time, quantitative PCR (qPCR) assays, samples were processed as previously described (35,36). To visualize the cellular expression sites of igf3 mRNA in zebrafish testis, in situ hybridization (ISH) was carried out as described previously (37), using DIG-labeled sense and antisense cRNA synthesized from a igf3-specific PCR product generated with primers 2878 -2879 (Supplemental Table 2). …”
Section: Testicular Gene Expressionmentioning
confidence: 99%
“…20 Another potential Leydig cell factor stimulating spermatogenesis could be insulin-like factor 3 (INSL3), though it has been shown to be dispensable for mouse spermatogenesis. 21 However, recent studies have shown that INSL3 can promote spermatogonial differentiation in zebrafish testis, 22,23 providing another example of evolutionary divergence in the hormonal regulation of gametogenesis. The spermatogenic effect of INSL3 thus seems to have been lost in mammals during evolution.…”
Section: Rodentsmentioning
confidence: 99%
“…), and as a germ cell proliferation factor in zebrafish (Assis et al . ). In addition, INSL3 possibly plays a role in sperm function as suggested by the detection of its receptor, relaxin family peptide receptor 2 (RXFP2) messenger RNA (mRNA) or protein in spermatozoa of rodents (Filonzi et al .…”
Section: Introductionmentioning
confidence: 97%